Análise das condições de acessibilidade nos bairros Residencial Nova Ituiutaba I, II, III e IV de Ituiutaba-MG: uma contribuição para a discussão sobre o direito à cidade - Guerra, Ana Letícia de Oliveira (2024)
This work focuses on the neighborhoods of Residencial Nova Ituiutaba I, II, III, and IV, aiming to analyze the accessibility conditions for people with disabilities or reduced mobility. The analysis was conducted considering the standards established by NBR 9050/2020, the National Urban Mobility Policy (Law 12.587/2012), and the Urban Mobility Plan of Ituiutaba (Law 4.507/2017). The justification for this study is directly related to the fundamental right to come and go, guaranteed by the Federal Constitution of 1988, as well as the urgent need to promote more inclusive and accessible cities. The rapid population growth of Ituiutaba, driven by the establishment of educational institutions and the expansion of the sugarcane industry, resulted in the construction of low-income housing, many of which are located in the city's peripheral areas. However, this process neglected the proper implementation of accessibility infrastructure, ignoring legal mobility standards and the rights of people with disabilities or reduced mobility. Throughout the research, the main barriers that hinder mobility in these neighborhoods were identified and analyzed, highlighting the obstacles residents face on a daily basis. A significant disconnect was found between the legal accessibility guidelines and their practical implementation. Despite the existence of urban planning instruments such as the Urban Mobility Plan and the Master Plan of Ituiutaba, the neighborhoods analyzed lack infrastructure that meets the basic needs of people with disabilities or reduced mobility. The research revealed recurring issues, such as uneven roads, inadequate slopes, poorly maintained sidewalks, and the absence of proper access ramps. These obstacles not only hinder pedestrian movement but also compromise the safety and right to mobility of these individuals, often making movement impossible. Among the most critical problems, garage access ramps stand out, creating steps that pose a significant challenge for people with disabilities or reduced mobility. Additionally, the absence of adequate signage at pedestrian crossings and in high traffic areas worsens the situation. The lack of pedestrian crossings, as well as the absence of traffic lights and appropriate ramps, represents a considerable risk for these individuals, who face greater difficulties when crossing the streets. This issue is exacerbated by drivers' lack of respect and the poor infrastructure of traffic signage on public roads. Another critical aspect identified in the study is the failure of the public transportation system, which, although equipped with vehicles with lift platforms, frequently presents problems such as broken elevators, preventing use by people with disabilities. The lack of accessibility at bus stops and shelters further aggravates the exclusion of these individuals. These problems highlight the non compliance with the fundamental principles of the right to the city. Therefore, the research highlights the importance of the Municipal Public Authority prioritizing accessibility in the urban planning of Ituiutaba, implementing effective measures to ensure the inclusion of all citizens.